â€œTHE INFLUENCE OF COMPANY FINANCIAL PERFORMANCE AND MACROECONOMIC FACTORS ON STOCK RETURNS (EMPIRICAL STUDY OF FOOD AND BEVERAGES COMPANIES LISTED IN INDONESIAN STOCK EXCHANGE AND LONDON STOCK EXCHANGE FOR THE YEAR 2012-2014)â€ - Nugraha, Aditya Ikhsan (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research aims to compare the influence of company financial performance and macroeconomic factors on stock returns for Food and Beverages companies listed in Indonesian Stock Exchange and London Stock Exchange. Population used in this research is 28 companies taken from LSE and 15 companies from IDX. The method used for selecting the samples is purposive sampling method. Based on the method used, this research found 10 companies from each stock exchange that can fulfill the sampling criteria. This research uses four different multiple regression models that each model consists of three company financial performance variables and one macroeconomic factor. The research finding presents a different result between IDX and LSE. In IDX, it is found that GDP is a strong indicator that can influence significantly on stock returns. Meanwhile in LSE, EPS along with current macroeconomic condition have become significant indicators toward stock returns.Â Keywords: stock returns, company financial performance, macroeconomic factorsÂ